Abandoning Fossil Fuel: How Fast and How Much. (10th April 2017) - Rezai, Armon; Van Der Ploeg, Frederick
Abstract : Keeping climate change within limits requires that most of the available carbon‐based energy sources need to be abandoned underground. We study how fast and how much this transition to carbon‐free energy needs to occur within a welfare‐maximizing Ramsey growth model of climate change. Our model also addresses the market failure in the development of clean energy which leads to an under‐provision of renewable energy, delays the transition time to the carbon‐free era and reduces the amount of dirty fuels locked up in situ . Optimal policy requires an aggressive renewables subsidy in the near term and a gradually rising carbon tax which falls in long run. We also study the transition timing and the performance of recently proposed policy rules for the carbon tax.